2000
DOI: 10.1253/jcj.64.358
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis Showing Less Cardiac Events in Post-Myocardial Infarction Patients Treated With Metoprolol

Abstract: This analysis was carried out to clarify the capacity of metoprolol to prevent cardiac events in Japanese post-myocardial infarction patients during a follow-up period of 16.3 months. Cardiac events occurred in 44 of 650 patients treated without beta-blockers (6.8%) and in 13 of 432 patients treated with metoprolol (3.0%), which represents a significant decline in the incidence of cardiac events among patients receiving metoprolol (p<0.01, odds ratio 0.43, 95% confidence interval 0.23-0.80). Because this was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…Nevertheless, in the present study we found that -blockers improved patient outcomes to a degree similar to that seen in Western populations. In our previous reports, 7,8 we concluded that -blockers effectively prevented cardiac events in patients with MI on the basis of data from 1,485 patients treated between 1986 and 1999. By increasing the number of cases to 1,896 and lengthening the study period up to 2002, we have been able to confirm the validity of the results of those earlier studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, in the present study we found that -blockers improved patient outcomes to a degree similar to that seen in Western populations. In our previous reports, 7,8 we concluded that -blockers effectively prevented cardiac events in patients with MI on the basis of data from 1,485 patients treated between 1986 and 1999. By increasing the number of cases to 1,896 and lengthening the study period up to 2002, we have been able to confirm the validity of the results of those earlier studies.…”
Section: Discussionmentioning
confidence: 89%
“…[7][8][9] Consequently, -blocker usage for patients with MI is markedly lower in Japan than in Western countries. Ischemic heart disease certainly differs between Japanese and Caucasians in some aspects; for example, coronary vasospasm occurs 3 times more frequently in Japan than in Western countries.…”
mentioning
confidence: 99%
“…The study population, design and method have been reported elsewhere. 11,12) Patient enrollment, study period, and exclusion criteria: Enrollment of this study population was initiated in 1986 and terminated in 1999. Pravastatin became available in 1990 in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…9 Consistent with those findings, we also found that increased use of ACEI likely contributes to improved long-term prognosis. The important role ofblockers for secondary prevention of MI has been pointed out repeatedly, 15,16 but their use is limited, especially among elderly patients. 17 Use of -blockers in our study population was high compared with that described by Heller et al, who reported that the use of -blockers among elderly survivors of acute MI (>65 years of age) increased from 39.6% in 1994 to 58.6% in 1997.…”
Section: Effective Secondary Prevention Of MImentioning
confidence: 99%